2015
DOI: 10.1016/j.jegh.2014.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of predictors of poor self-rated health in a 23-year cohort of earthquake survivors in Armenia

Abstract: Long-term prospective studies exploring general health outcomes among disaster survivors are rare. Self-rated health (SRH) - a proven correlate of morbidity and mortality prognosis - was used to investigate predictors of perceived health status among a 23-year cohort of survivors of 1988 Spitak earthquake in Armenia. A geographically-stratified subsample of 725 adults from a larger initial cohort was followed during the period of 1990-2012. A logistic regression model identified predictors of SRH. Adjusted rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 69 publications
(101 reference statements)
0
10
1
Order By: Relevance
“…However, the risk of depressive symptoms experienced by poor self‐rated health respondents in this study was lower than in previous studies. In this study, poor self‐rated health doubled the depressive symptoms risk, while other studies reported that poor self‐rated health increased the risk odds depressive symptoms by three to four‐fold 47,49 . Differences in respondent characteristics may be related to this finding.…”
Section: Discussioncontrasting
confidence: 51%
“…However, the risk of depressive symptoms experienced by poor self‐rated health respondents in this study was lower than in previous studies. In this study, poor self‐rated health doubled the depressive symptoms risk, while other studies reported that poor self‐rated health increased the risk odds depressive symptoms by three to four‐fold 47,49 . Differences in respondent characteristics may be related to this finding.…”
Section: Discussioncontrasting
confidence: 51%
“…In the current study, SRH was not associated with stress, gender or being a smoker. The number of stressful life events experienced is associated with poorer SRH [ 73 ]. A study of black American adults reported a significant association between SRH and stress [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Cai et al, depression is the strongest predictor of SRH, especially in women and elderly people (16). There are reports indicating that SRH is also related to the number of stressful life situations (23) and distress (24), whereas social support (23) and self-efficacy (24) are considerable protective factors.…”
Section: Introductionmentioning
confidence: 99%
“…Medical factors related to SRH include depression (16) and the occurrence of multiple diseases (23). However, the impact of the last factor is ambiguous.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation